EFEK MODERASI COUNTRY OF ORIGIN PADA PENGARUH KUALITAS PRODUK DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP TOSHIBA - Erdawati Erdawati; Asraf Asraf (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
On mobile computers market in Indonesia, including in Simpang Empat West Pasaman, there are many product from many country by various brands. The high competition requires manufacturers and distributors to implement the marketing strategies. To implement these strategies required a good understanding of the factors that influence the decision purchase. This study analyzed the moderating effect of country of origin variable on the influence of product quality and brand equity on Toshiba purchasing decisions in Simpang Empat Pasaman Barat. This studies show that the product and brand equity as partially or simultaneously positive and significant influence on purchasing decisions. Country of origin moderated the influence of the quality of products on purchasing decisions and also brand equity influence on purchasing decisions. The results of this study imply that in order to improve the purchase decision of Laptop Toshiba, can be done by increasing again product quality and brand equity. Special to the store vendors, recommended to sell products made in Japan as a priority, because the computers made in Japan is perceived as a high quality product. Keywords: Product, Brand Equity, Country Of Origin and Purchase Decision